Sanitary improvement and mortality decline in Sydney, New South Wales, 1857–1906: drinking water and dunnies as determinants. Issue 2 (3rd April 2019) - de Looper, Michael Willem; Booth, Heather; Baffour, Bernard
ABSTRACT: Two corollaries of the rapid growth of Sydney, New South Wales, during the nineteenth century were degradation of the water supply and inadequate sanitation. Reform was slow to arrive: a new scheme began to supply clean water from 1886, while connections to the sewerage system increased gradually from less than 25% of the population in 1889 to 80% by 1906. Examination of mortality trends during 1857–1906 shows that decline began in the mid 1880s, led by falls in under-five mortality from water-related communicable diseases. By 1906, the mortality differential between Sydney and the rest of New South Wales had all but disappeared. Based on statistical modelling, we conclude that the provision of a new source of clean water was the key factor in bringing about the decline in water-related mortality in Sydney. Improved sewerage coverage had less effect on mortality decline, coming as it did after the provision of clean water, although the role of sewerage infrastructure diffusion remains unknown.